Glorifier dans la pierre : nouvelles observations sur la production épigraphique de Guillaume Philandrier (1505-1565) à Rodez - Caroline de Barrau-Agudo (Les Cahiers de Framespa)
The construction of the Gothic cathedral of Rodez was begun in 1277 and not finished until the 1580s. In 2006 archaeological work brought to light 2500 fragments of sculpture, the results of voluntary destruction of medieval and modern statuary during the Revolutionary period. Among these fragments are inscriptions of texts written by Guillaume Philandrier, canon of Rodez and secretary to the Cardinal Archbishop Georges d’Armagnac. This paper will examine the results of an analysis of these fragments and will also examine historiographic problems in the light of the discovery of an archival document with relevance to these inscriptions. This will lead to the question of Philandrier’s love of monumental epigraphy, taking into account his biography documented now by the numerous studies of Madame Frédérique Lemerle. An earlier paper given orally at a study day is here recast and developed more fully in this written version, allowing the discovery of that document and its important contents to be set in the wider context of Humanism and of sixteenth-century artistic production. Further observations are also made on epigraphy and on architectural books.